2021
DOI: 10.1007/s10562-020-03519-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of CO2 During Oxidative Dehydrogenation of Propane Over Bulk and Activated-Carbon Supported Cerium and Vanadium Based Catalysts

Abstract: CeO2, V2O5 and CeVO4 were synthesised as bulk oxides, or deposited over activated carbon, characterized by XRD, HRTEM, CO2-TPO, C3H8-TPR, DRIFTS and Raman techniques and tested in propane oxidative dehydrogenation using CO2. Complete oxidation of propane to CO and CO2 is favoured by lattice oxygen of CeO2. The temperature programmed experiments show the ~ 4 nm AC supported CeO2 crystallites become more susceptible to reduction by propane, but less prone to re-oxidation with CO2 compared to bulk CeO2. Catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Balogun et al 126 The catalytic activity of surface VO x can also be further regulated by doping with metal oxides such as CeO x , FeO x and CrO x . By using active carbon as a support, Djinović et al 132 prepared a series of nVO x /AV and nCeVO 4 /AC catalysts and tested their activity in CO 2 -OPDH. They found that the CeVO 4 content was positively correlated with the catalytic activity and propene selectivity.…”
Section: Supported Vanadium Oxidesmentioning
confidence: 99%
“…Balogun et al 126 The catalytic activity of surface VO x can also be further regulated by doping with metal oxides such as CeO x , FeO x and CrO x . By using active carbon as a support, Djinović et al 132 prepared a series of nVO x /AV and nCeVO 4 /AC catalysts and tested their activity in CO 2 -OPDH. They found that the CeVO 4 content was positively correlated with the catalytic activity and propene selectivity.…”
Section: Supported Vanadium Oxidesmentioning
confidence: 99%
“…species by CO 2 at 750 °C. Subsequently, Djinovic ´et al [59] utilized an electron-rich active carbon (AC) to adjust the electron environment of CeO 2 and prepared a CeO 2 /AC catalyst, which could achieve the CO 2 -ODHP. The catalyst was found to be susceptible to the dehydrogenation of propane, and especially a catalyst with large CeO 2 size was beneficial for re-oxidation with CO 2 .…”
Section: Cerium-based Rare Metal Catalystsmentioning
confidence: 99%
“…The UV-Vis analysis showed that CO 2 addition may have retained the higher oxidation state of vanadium species. Further investigations were conducted from different catalyst design, such as surface doped vanadia catalysts (7 V7 W, 7 V5Mo, and 7 V4Cr), [56] mixed oxides (WO x -VO x /SiO 2 [57] and CeVO x [58] ), modified supports (VO x /La 2 O 3 -g-Al 2 O 3 , [59] nV-MSNSs, [60] and nV-MCM-41 [61] ), and the specific preparation method using 3D printing. [44,[62][63][64] However, designing an efficient vanadium-based catalyst remains challenging due to the controversy over the active site (oxidized vanadium, oligomeric vanadium, and V 2 O 5 crystallite) in various complex systems.…”
Section: Development Of Metal Oxides In Co 2 à Odpmentioning
confidence: 99%